BOMBO CAKALANG TEKNOLOGI PENANGKAPAN IKAN BOMBO CAKALANG DI PERAIRAN IWOIMENDAA KABUPATEN KOLAKA SULAWESI TENGGARA - Bubun, Rita L.; Mahmud, Amir; Alam, Riswal (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2021)
“Bombo cakalang” is one type of traditional fishing gear used to catch skipjack in Iwoimendaa Water Kolaka Regency, Southeast Sulawesi.  The contruction of “bombo cakalang” is the one net that floating on the surface water. The research objectives was to describe about the fishing gear technology of “bombo cakalang” related to contruction, the methode of fishing, and fishing ground of skipjack in Iwoimendaa Water Kolaka Regency. The research method use is a survey method by collecting the data on result of observation at the study site.  Data analyze are using qualitative and quantitative descriptive.  The results showed that (1) the contruction of “bombo cakalang” are composed of net with hanging ratio (E1) in 46,59% and E2 in 0,31%, net frame (float), line hauler, and barrier stake, buoyancy force (B) in 1,037 Kgf dan sinking force (S) in 0,303 Kgf; (2)  the methode of fishing are trapping, tangling and deception; The fishing ground are the coastal Bone Bay, coordinates in 03°778’77”-03°791’44” Southern Latitude and 21°068’32” - 121°110’07” East Longtitude,  sea surface temperature (SST) in 25°C - 28°C and the salinity in 31‰ - 33‰. Key word: “bombo cakalang”, Iwoimendaa, skipjack